Campanhas eleitorais e democracia : o diálogo a partir do direito de resposta - Piva, Otávio (2014)
This thesis studies the importance of electoral campaigns for democracy and political phenomena generated by the Electoral Court to grant to the offended candidate the Response Right. In a precursor form, it verifies the hypothesis of right of reply given by the Electoral Court to be leading candidates to talk about cutting themes, providing the voter's choices important to map information. The thesis also crosses data from polls and the admission of shares on TSE in order to check whether there is a relationship between the position of the candidates in the polls on voting intentions, conducting negative campaigns and the inflow of orders right response. The thesis also aims to inset the institution of Response Right as a phenomenon to be studied by Social Sciences. Relating election campaigns for democracy and the theory that supports the possibility of achieving accountability as measuring the quality factor of democracies, one comes to the concepts of dialogue and convergence, recognizing that informed voter matters to democracy. Moreover, it discusses the importance, or not, of dialogue,or convergence, to the electoral victory, exemplifying through Brazilian models of free electoral propaganda on television. This literature review is contextualized in Brazilian peculiarity parties have available the Free Time Election Propaganda and the Right of Reply. At the end, it presents the resolution of the central problem of research on the occurrence of dialogue in campaigns from the Right of Reply is presented shows the themes that generated more requests for right of reply, granted or not, the presidential campaigns 2002-2010 and crossing all the data, is established if there is a relation with the position of the candidates in the polls of voting intention.